Formation of metal-organic ligand complexes affects solubility of metals in airborne particles at an urban site in the Po valley. (February 2020) - Tapparo, Andrea; Di Marco, Valerio; Badocco, Denis; D'Aronco, Sara; Soldà, Lidia; Pastore, Paolo; Mahon, Brendan M.; Kalberer, Markus; Giorio, Chiara
Abstract: Metals in atmospheric aerosols play potentially an important role in human health and ocean primary productivity. However, the lack of knowledge about solubility and speciation of metal ions in the particles or after solubilisation in aqueous media (sea or surface waters, cloud or rain droplets, biological fluids) limits our understanding of the underlying physico-chemical processes. In this work, a wide range of metals, their soluble fractions, and inorganic/organic compounds contained in urban particulate matter (PM) from Padua (Italy) were determined. Metal solubility tests have been performed by dissolving the PM in water and in solutions simulating rain droplet composition. The water-soluble fractions of the metal ions and of the organic compounds having ligand properties have been subjected to a multivariate statistical procedure, in order to elucidate associations among the aqueous concentrations of these PM components in simulated rain droplets. In parallel, a multi-dimensional speciation calculation has been performed to identify the stoichiometry and the amount of metal-ligand complexes theoretically expected in aqueous solutions. Both approaches showed that the solubility and the aqueous speciation of metal ions were differently affected by the presence of inorganic and organic ligands in the PM. The solubility of Al, Cr, and Fe was strongly correlated to the concentrations of oxalic acid, as their oxalate complexes represented the expected dominant species in aqueous solutions. Oxalates of Al represented ∼98% of soluble Al, while oxalates of Cu represented 34–75% of the soluble Cu, and oxalates of Fe represented 76% of soluble Fe. The oxidation state of Fe can strongly impact the speciation picture. If Fe is present as Fe(II) rather than Fe(III), the amount of Cr and Cu complexed with diacids can increase from 75% to 94%, and from 32% to 53%, respectively. For other metals, the solubility depended on the formation of soluble aquo-complexes, hence with a scarce effect of the organic ligands. An iron-oxalate complex was also directly detected in aerosol sample extracts. Highlights: Solubility and speciation of metal ions released by PM in aqueous solutions simulating fog and rainwater was investigated. Solubility of Al, Cr, and Fe was strongly correlated to the concentrations of oxalate. Succinate and malonate moderately affected the solubility of Cr. Cu, Zn, Mn, Pb, and Ni were partly complexed by organic acids in solution. Direct detection of an iron-oxalate complex was also performed in aerosol sample extracts.